Caesarean section in Benin and Mali: increased recourse to technology due to suffering and under-resourced facilities. (June 2020) - Schantz, Clémence; Aboubakar, Moufalilou; Traoré, Abou Bakary; Ravit, Marion; de Loenzien, Myriam; Dumont, Alexandre
Abstract: In line with policies to combat maternal mortality, the medicalization of childbirth is increasing in low-income countries, while access to healthcare services remains difficult for many women. High caesarean section rates have been documented recently in hospitals in Mali and Benin, illustrating an a-priori paradoxical situation, compared with low caesarean section rates in the population. Through a qualitative approach, this article aims to describe the practice of caesarean section in maternity wards in Bamako and Cotonou. Workshops with obstetricians and midwives; participant observation inside labour rooms; and in-depth interviews with caregivers, patients and policy makers have indicated increased recourse to caesarean section due to women's and caregivers' suffering and under-resourced facilities. Within these procedures, two types of caesarean section were documented: 'maternal distress caesarean section' and 'preventive caesarean section'. The main reasons for these caesarean sections are maternal fear and pain, and a lack of resources. Inadequately resourced facilities lead to staff suffering and ethical breakdowns, and encourage the inappropriate use of technology. The policy of access to free caesarean section procedures exacerbates the issue of non-medically-justified caesarean sections in these countries. The overuse of caesarean section is particularly alarming in countries with high fertility as it constitutes a danger to both mothers and babies in the short and long term. Currently, conditions are in place in Benin and Mali for an increase in non-medically-justified caesarean sections. In the short term, such an increase could constitute a new burden for these two sub-Saharan countries, where maternal mortality is high. Highlights: There is increased recourse to caesarean section in health facilities in Mali and Benin Some women request a caesarean section during their labour because they are suffering Inadequately resourced facilities lead to staff suffering and overuse of technology